PFOA and PFOS diffusion through LLDPE and LLDPE coextruded with EVOH at 22 °C, 35 °C, and 50 °C. (November 2020) - Di Battista, V.; Rowe, R. Kerry; Patch, D.; Weber, K.
Highlights: First diffusion study of per- and polyfluoroalkyl substances through geomembranes. Provides parameters for calculating the impact of PFAS in MSW leachate to the environment. Reports low flux of PFOA through LLDPE and LLDPE coextruded with EVOH geomembranes. Reports low flux of PFOS through LLDPE and LLDPE coextruded with EVOH geomembranes. Abstract: Diffusion of perfluorooctanoate (PFOA) and perfluorooctane sulfonate (PFOS) through 0.1 mm and 0.75 mm LLDPE and 0.1 mm and 0.75 mm LLDPE coextruded with ethyl vinyl alcohol (denoted as CoEx) at room temperature (23 °C), 35 °C, and 50 °C is examined. These tests had negligible source depletion throughout the monitoring period, indicating limited contaminant partitioning and diffusion through the LLDPE. At 483 days, 23 °C receptor PFOA and PFOS concentrations, cr, were <8 μg/L ( cr / co  < 3.2 × 10 −4 ) for all tests, and at 399 days elevated temperature receptor concentrations were < 0.4 μg/L ( cr / co  < 1.6 × 10 −5 ) at 35 °C and <0.5 μg/L ( cr / co  < 2.0 × 10 −5 ) at 50 °C for both PFOA and PFOS. LLDPE partitioning coefficient, Sgf was 0.9–1.4 (PFOA) and 2.8–5.3 (PFOS) based on sorption tests at 23 °C. Based on the best estimates of permeation coefficient, Pg CoEx, for CoEx was consistently lower than Pg LLDPE . For PFOA, CoEx had Pg CoEx  < 0.26 × 10 −16 m 2 /s at 23 °C, <11 × 10 −16 m 2 /s (35 °C), and < 10 × 10 −16 m 2 /s (50 °C) while LLDPE had Pg LLDPE  < 3.1 × 10 −16 m 2 /s (23 °C), <13 × 10 −16 m 2 /s (35 °C), and <19 × 10 −16 m 2 /s (50 °C). For PFOS, CoEx and LLDPE had Pg CoEx  < 0.55 × 10 −16 m 2 /s and Pg LLDPE  < 3.2 × 10 −16 m 2 /s (23 °C), Pg CoEx  < 8.3 × 10 −16 m 2 /s and Pg LLDPE  < 40 × 10 −16 m 2 /s (35 °C), and Pg CoEx  < 8.2 × 10 −16 m 2 /s and Pg LLDPE  < 52 × 10 −16 m 2 /s (50 °C). These values are preliminary and may change (e.g., decrease) as more data comes available over time. The Pg values deduced for PFOA and PFOS are remarkably lower than those reported for other contaminants of concern, excepting BPA, which exhibits similar behaviour.